The Evolution of Society An Information-Processing Perspective - Aslaksen, Erik W. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book covers the work of Erik W. Aslaksen who continues to develop the view of society and its evolution published in earlier work - The Social Bond (Springer 2018), The Stability of Society (Springer 2020), and Measures of Social Evolution (Springer 2021), bringing together core material of that work with the results of recent investigations in order to present the evolution of society as an integrated and continuous story leading right up to the present time. A story of human action driven by our beliefs, desires, and an ideology arising out of our ability to transform and exploit our environment through the development and application of technology. The distinguishing feature of the work is the treatment of society as an information-processing system and applying the system methodology for handling complexity, as it is applied, e.g., in engineering. This focus on information is particularly pertinent in the current circumstances, where the world has arrived at a critical point in its history through the conjunction of a number of issues that appear to be spiralling out of control: Global warming and the associated climate change, the destruction of our environment through such processes as land clearing and industrialisation with associated loss of biodiversity, the rapidly increasing visibility of the inequality in the quality of life with associated tensions, and above all, the determination of the US-led Western alliance to cling to its hegemonial role, apparently at all cost. With the sophistication and proliferation of nuclear weapons, the latter has the potential to bring on the end of civilisation as we know it. The resolution of any of these issues depends on the information available to all parties involved, and hence, the availability and quality of information is seen as the crucial and overarching issue of the present time. A number of aspects of this issue, including the role of education, economic inequality, and the control of the media, aretreated in some detail, and proposals for some small steps in the right direction are put forward.
1. Introduction -- 2. Evolution -- 3. The Two Views -- 4. Model of the Individual -- 5. The Interaction -- 6. Operating Conditions of the Collective Intelligence -- 7. Adaptive Action -- 8. Technology -- 9. The Role of Education -- 10. Measures of Evolution -- 11. Tension and Instability -- 12. Modifying the Nation -- 13. The World Society.
Keywords: Dynamics; Nonlinear theories; Sociology; System theory; Applied Dynamical Systems; Sociology; Complex Systems